LINE-1 and EPAS1 DNA methylation associations with high-altitude exposure. Issue 1 (2nd January 2019) - Childebayeva, Ainash; Jones, Tamara R.; Goodrich, Jaclyn M.; Leon-Velarde, Fabiola; Rivera-Chira, Maria; Kiyamu, Melisa; Brutsaert, Tom D.; Dolinoy, Dana C.; Bigham, Abigail W.
ABSTRACT: Recent discoveries indicate a genetic basis for high-altitude adaptation among human groups who have resided at high altitude for millennia, including Andeans, Tibetans, and Ethiopians. Yet, genetics alone does not explain the extent of variation in altitude-adaptive phenotypes. Current and past environments may also play a role, and one way to determine the effect of the environment is through the epigenome. To characterize if Andean adaptive responses to high altitude have an epigenetic component, we analyzed DNA methylation of the promoter region of EPAS1 and LINE-1 repetitive element among 572 Quechua individuals from high- (4, 388 m) and low-altitude (0 m) in Peru. Participants recruited at high altitude had lower EPAS1 DNA methylation and higher LINE-1 methylation. Altitude of birth was associated with higher LINE-1 methylation, not with EPAS1 methylation. The number of years lived at high altitude was negatively associated with EPAS1 methylation and positively associated with LINE-1 methylation. We found four one-carbon metabolism SNPs ( MTHFD1 rs2236225, TYMS rs502396, FOLH1 rs202676, GLDC rs10975681) that cumulatively explained 11.29% of the variation in average LINE-1 methylation. And identified an association between LINE-1 methylation and genome-wide SNP principal component 1 that distinguishes European from Indigenous American ancestry suggesting that European admixture decreases LINE-1 methylation. Our results indicate that both current and lifetime exposure to high-altitude hypoxia have an effect on EPAS1 and LINE-1 methylation among Andean Quechua, suggesting that epigenetic modifications may play a role in high-altitude adaptation.